Konstitusionalitas Kemandirian Lembaga Penyelenggara Pemilihan Umum (Analisis Putusan Mahkamah Konstitusi Nomor 81/PUU-IX/2011) - Reza Syawawi (Universitas Medan Area, 2020)
This article analyses the Constitutional Court Decision No 81/PUU-IX/2011 that strengthen the existing of Election Management Body in Indonesia as an independent body. The problem statement focused on the Constitutional Court’s consideration on putting the idea of the independence of electoral management body as stated on UUD 1945. The trend of election management body in other country shows that democratic countries are leaving the partisan type of election management body. This argumentation depart from the belief that the independence election management body will guarantee the more democratic election. The emergence of the provision in the Law No 15/2011 that accommodate the political party member to become the commissioner of the election management body considered as inconsistent with the original intent of the amendment of UUD 1945 that require the independent election management body. However the formulation of Article 22E Paragraph (5) UUD 1945 is not explain explicitly so it raised the different interpretation from the law maker. As of that, there is a need to clarify the criteria of the independence of election management body in the UUD 1945